Comparative analysis of the structure of temporomandibular joint in human and rabbit - Tomasello, Giovanni; Sorce, Alessandra; Mazzola, Margherita; Barone, Rosario; Lo Piccolo, Chiara; Farina, Felicia; Zummo, Giovanni; Carini, Francesco (Acta Biomedica Atenei Parmensis, 2017)
In order to increase knowledge on the morphology and structure of the articular disc of the TMJ for a better understanding of the functional role of the same, it proceeded with an investigation on histological samples in the block of ‘TMJ and periarticular tissues of adult rabbits and human fetuses at different stage of development.